Land Rights - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
This documents contains technical information related experiences of people who have struggled ? and sometimes failed - to keep their rights to their land. There are examples from Cameroon, Malawi, Zimbabwe and The Gambia.